Theoretical-methodological model for the analysis of public policies that promote sustainable tourism and environmental conservation in the Valle de Bravo Water Sanctuary, Mexico - Ayala-Arzate, Jorge Adonay (2025)
The objective is to provide a theoretical-methodological model that analyzes the issues and interventions of the public, social, and private sectors in the design of public policies to promote sustainable tourism and environmental conservation in the Santuario del Agua Valle de Bravo State Park, located in the State of Mexico. Methodologically, the model was developed using both theoretical and empirical elements; the former refers to sustainable tourism as the main category, with sustainability, environmental conservation, and public policies as subcategories. The empirical elements included observation and interviews with key stakeholders involved in tourism and environmental conservation within the park. The model linked these subcategories to structural and positional dimensions, which facilitated engagement with the actors. The comprehensive analysis drew on the assumptions of the Public Policy Network Approach, identifying interaction, coordination, and the exchange of information and resources among the members of the network formed around public policies. The result was a model that serves as a tool for analyzing the reality in these areas by visualizing the connections among those involved in tourism and environmental conservation. It is expected to serve as a reference for addressing various realities in different contexts, while respecting and adapting to their particularities. The model concludes that there are limitations to the scope of public policies in promoting sustainable tourism and environmental conservation in the park, due to a lack of commitment from the public sector to fulfill its responsibilities, as well as limited resources and prevailing interests.